Influence of Additives on the Viscoelastic Behavior of Asphalt Concrete - Saad Issa Sarsam (Britain International for Academic Research (BIAR) Publisher, 2022)
Implication of mineral additives into the asphalt concrete mixture can influence the viscoelastic behavior; change the density, gradation, and strength properties. In the present investigation, fly ash and silica fumes were added to the asphalt concrete mixture. Slab samples were compacted with the aid of laboratory roller, and then beam specimens were sawed from the slab samples. The asphalt concrete beam specimens were subjected to repeated flexural stresses through the four-points bending test at 20℃ and under 400 micro-strain level until failure. The influence of the additives was monitored and compared. It was concluded that the phase angle, flexural stiffness, and the fatigue life declines while the cumulative dissipated energy increases after implication of the additives. However, the silica fumes additives exhibit a significant impact on the viscoelastic properties as compared with the control or the fly ash treated mixtures.